1996
DOI: 10.1016/s0378-1097(96)00427-2
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of an exo-polygalacturonase from the tomato vascular wilt pathogen Fusarium oxysporum f.sp. lycopersici

Abstract: An exo-polygalacturonase (EC 3.2.1.15) was purified to apparent homogeneity from cultures of Fusarium oxysporum fsp.lycopersici on synthetic medium supplemented with citrus pectin, using preparative isoelectric focusing. The enzyme, denominated PG2, had an apparent A4, of 74 000 Da upon SDS-PAGE. The pI of the main PG2 isoform was 4.5, and pH and temperature optima were 5.0 and WC, respectively. PG2 hydrolyzed polygalacturonic acid in an exo-manner, as demonstrated by anaysis of degradation products. The enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…Similar results were reported for purified PG produced by mesophilic fungi such as A. niger (Sakamoto et al 2002), B. cinerea (Cabanne and Donè che 2002), F. oxysporum (Pietro and Roncero 1996) and the thermophilic fungus T. lanuginosus (Sathish-Kumar and Palanivelu, 1999).…”
Section: Classification Of Enzymesupporting
confidence: 82%
See 1 more Smart Citation
“…Similar results were reported for purified PG produced by mesophilic fungi such as A. niger (Sakamoto et al 2002), B. cinerea (Cabanne and Donè che 2002), F. oxysporum (Pietro and Roncero 1996) and the thermophilic fungus T. lanuginosus (Sathish-Kumar and Palanivelu, 1999).…”
Section: Classification Of Enzymesupporting
confidence: 82%
“…This value is similar to exo-enzymes secreted by some other fungi, which are in the range 28-43 kDa, such as PGs from Fusarium moniliforme (30.6 kDa), Rhizopus arrhizus (30 kDa), Rhizopus sp. (32 kDa), Rhizopus oryzae (31 kDa), Verticillium albo-atrum (37 kDa), Venturia pirina (43 kDa) (Elegado and Fujio 1994;Huang and Mahoney 1999;Isshiki et al 2000) and lower than the PGs produced by Sclerotinia sclerotiorum (Riou et al 1992;Pietro and Roncero 1996;Sakamoto et al 2002;Mohamed et al 2003;Saito et al 2004;Niture and Pant 2004). The homogeneity of PG was confirmed by isoelectric focusing with a single band at pI 7.8 (Table 2).…”
Section: Homogeneity Mr and Pi Valuesmentioning
confidence: 90%
“…Using concanavalin A and tunicamycin, Kawano et al (10) elegantly showed the importance of the glycosylation process for the secretion of pectinases produced by P. frequentans. The molecular masses of Exo-PG II (63 kDa) and Exo-PG III (79 kDa), determined by gel filtration were similar to those reported for other fungal extracellular exopolygalacturonases, such as the 68 kDa enzyme from Sclerotinia sclerotiorum (18), the 60 kDa enzyme from Cochliobolus carbonum (21), the 78 kDa enzyme from Aspergillus tubingensis (11), and the 74 kDa enzyme from Fusarium oxysporum f. sp (7). The fact that the molecular masses of Exo-PG I, Exo-PG II and Exo-PG III were higher than that of Endo-PG I produced by this fungus (20 kDa) has been also observed in other fungi by Kester et al (11), suggesting that this may be a general property of fungal exopolygalacturonases.…”
Section: Resultssupporting
confidence: 79%
“…Glucose repression is a common phenomenon in the regulation of fungal PGs; glucose acts as a catabolite repressor for PG production in numerous fungi including Fusarium oxysporum, Fisarium moniliforme, Botrytis cinerea and Saccharomyces cerevisiae (Blanco et al 1994;Di Pietro & Roncero 1996a;Wubben et al 2000;Niture et al 2006). Naidu & Panda (2004) reported recently on the roles of different carbon sources and other fermentation parameters for the production of pectinases including PG.…”
Section: Regulation Of Fungal Pgs Productionmentioning
confidence: 99%